The Influence of System User Ability and Top Management Support on Accounting Information System Performance - Yusi Lusiansyah (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
Digitization of technology in hospitals is needed to facilitate services and reporting. Especially RSUD Soreang Bandung Regency has become a Public Service Agency which has consequences for accountability and auditability so that it requires the support of a perfectly integrated accounting information system. So the measurement of the factors that influence the success of the performance of the accounting information system needs to be done quickly and precisely. This is the background of the purpose of this study, namely to determine how much influence the ability of system users and top management support to the performance of accounting information systems at RSUD Soreang, Bandung Regency. The research method used is quantitative, descriptive and verification using primary and secondary data. Other data analysis techniques used are classical assumption test, multiple linear regression, regression coefficient and coefficient of determination. The results showed that the ability of system users and top management support partially or simultaneously had a significant and positive effect on the performance of the accounting information system.